1997
DOI: 10.1159/000109673
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Vitamin C, Beta-Carotene and 30-Year Risk of Stroke: Results from the Western Electric Study

Abstract: The relations of dietary antioxidants vitamin C and beta-carotene to 30-year risk of stroke incidence and mortality were investigated prospectively in the Chicago Western Electric Study among 1,843 middle-aged men who remained free of cardiovascular disease through their second examination. Stroke mortality was ascertained from death certificates, and nonfatal stroke from records of the Health Care Financing Administration. During 46,102 person-years of follow-up, 222 strokes occurred; 76 of them were fatal. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
32
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 26 publications
0
32
0
1
Order By: Relevance
“…9 In 3 other cohort studies, 8,12,13 intake of ␤-carotene was unrelated to risk for stroke. Furthermore, in large-scale intervention trials ␤-carotene supplementation either had no effect on risk for stroke 29 or had no effect on the risk for cerebral infarction but increased risk for intracerebral hemorrhage.…”
Section: Hirvonen Et Al Antioxidant Intake and Stroke Risk In Male Smmentioning
confidence: 95%
See 1 more Smart Citation
“…9 In 3 other cohort studies, 8,12,13 intake of ␤-carotene was unrelated to risk for stroke. Furthermore, in large-scale intervention trials ␤-carotene supplementation either had no effect on risk for stroke 29 or had no effect on the risk for cerebral infarction but increased risk for intracerebral hemorrhage.…”
Section: Hirvonen Et Al Antioxidant Intake and Stroke Risk In Male Smmentioning
confidence: 95%
“…Inverse associations with the risk for stroke have been observed for flavonols and flavones, 8 carotenoids, 9 and vitamin C. 10,11 In contrast, studies also exist in which no clear associations with dietary antioxidants were found. 12,13 One reason for the inconsistent results may be that these studies have examined only the associations with total stroke. Different subtypes of stroke, however, have different etiopathologies 14 and thus most likely also have different associations with dietary antioxidants.…”
mentioning
confidence: 99%
“…1,4 Some population studies have suggested that increased consumption of fruits and vegetables decreases the risk of atherosclerotic cardiovascular diseases (CVD), including cerebrovascular strokes, 5-9 whereas 1 study did not confirm this association. 10 These findings led to a great interest in the role of antioxidative vitamins in CVD, including cerebrovascular strokes.…”
mentioning
confidence: 99%
“…H igh amounts of fruits and vegetables in the diet 1,2 as well as diets rich in antioxidant vitamins 3 have been associated with decreased incidence of stroke. A similar inverse relation has been observed between serum concentrations of antioxidant vitamins and the risk of fatal stroke.…”
mentioning
confidence: 99%